Sockeye salmon spawners in the basin of Nachikinskoye Lake (south-western Kamchatka): biology and abundance - O. M. Zaporozhets; G. V. Zaporozhets (Известия ТИНРО, 2022)
State of the spawning part of the sockeye salmon population in Lake Nachikinskoye is characterized. Adults of the early race enter the lake from the sea in spring and early summer, mature at a depth and spawn from July to late August in three different loci — creeks, springs and lake, forming the corresponding ecotypes. The late race representatives enter the lake in July-August, mature, and spawn until December in the same loci. The races differ in age structure, size and fecundity. Males dominate in both races, with a growing proportion of small-sized individuals. According to the materials of aero surveys, the number of fish on the spawning grounds decreased gradually until 2016. Recent data are presented for the number of sockeye salmon belonged to early and late races on certain spawning grounds in the lake basin, based on results of quadrocopter surveys in 2018–2021. The number of the early race spawners was ~100–400 × 103 ind., late race ~300–500 × 103 ind.; the fluctuations were not synchronous between the races. These great spawning stocks require reliable protection and detailed annual monitoring to predict further changes.